2019
DOI: 10.1007/s12597-019-00380-5
|View full text |Cite
|
Sign up to set email alerts
|

Strategic analysis of the Indian agri-food supply chain

Abstract: Indian agri-food supply chain (AFSC) is highly unorganized in terms of flow of products, funds, and information, resulting in low profitability of farmers. In this paper, we have identified various internal factors (strengths and weaknesses) and external factors (opportunities and threats) of AFSC to make a strategic viewpoint. Based on the identified factors, questionnaire are prepared and circulated among experts from academics and industries to prioritize the identified factors. Further, analytical hierarch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 30 publications
0
17
0
2
Order By: Relevance
“…On the other hand, despite agriculture being exempted from the lockdown restrictions, labor and input availability were observed as major bottleneck areas as reported by the farmers. The food supply chain in India is disorganized, fragmented and inefficient due to several challenges like small landholdings, lack of infrastructure like post-harvest storage and processing units, among many others (Parwez, 2016;Meena et al, 2019). These challenges further magnify the impact of both biotic and abiotic risks as mentioned in the news articles.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, despite agriculture being exempted from the lockdown restrictions, labor and input availability were observed as major bottleneck areas as reported by the farmers. The food supply chain in India is disorganized, fragmented and inefficient due to several challenges like small landholdings, lack of infrastructure like post-harvest storage and processing units, among many others (Parwez, 2016;Meena et al, 2019). These challenges further magnify the impact of both biotic and abiotic risks as mentioned in the news articles.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Ali et al (2019) presented a framework for risk evaluation in food supply chains. Similarly, Meena et al (2019) studied an Indian agro-food supply chain problem and identified the important factors affecting the agro-food supply chain using Fuzzy analytic hierarchy process (AHP) method. Chen et al (2020) designed a knowledge network examining lean supply chain decisions with respect to agro-food industry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sayareh & Alizmini (2014) focused to balance the utmost dominant decision-making-criteria by TOPSIS and the optimized container seaport selection by the AHP method according to the significant factors of port selection. Meena et al (2019) used AHP and fuzzy AHP to rank the identified SWOT factors in the agro-food supply chain in the Indian context. Ugboma et al (2006) used the analytical hierarchy process (AHP) method to form a better framework.…”
Section: Solution Approachmentioning
confidence: 99%